Multifunctional roles of the mammalian CCR4–NOT complex in physiological phenomena - Shirai, Yo-Taro; Suzuki, Toru; Morita, Masahiro; Takahashi, Akinori; Yamamoto, Tadashi (Frontiers in Genetics, 2014)
The carbon catabolite repression 4 (CCR4)–negative on TATA-less (NOT) complex serves as one of the major deadenylases of eukaryotes. Although it was originally identified and characterized in yeast, recent studies have revealed that the CCR4–NOT complex also exerts important functions in mammals, -including humans. However, there are some differences in the composition and functions of the CCR4–NOT complex between mammals and yeast. It is noteworthy that each subunit of the CCR4–NOT complex has unique, multifunctional roles and is responsible for various physiological phenomena. This heterogeneity and versatility of the CCR4–NOT complex makes an overall understanding of this complex difficult. Here, we describe the functions of each subunit of the mammalian CCR4–NOT complex and discuss the molecular mechanisms by which it regulates homeostasis in mammals. Furthermore, a possible link between the disruption of the CCR4–NOT complex and various diseases will be discussed. Finally, we propose that the analysis of mice with each CCR4–NOT subunit knocked out is an effective strategy for clarifying its complicated functions and networks in mammals.